2014
DOI: 10.1136/jnnp-2013-306724
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anterograde amnesia following limbic encephalitis associated with antibodies to the voltage-gated potassium channel complex

Abstract: The results show that, despite broad cognitive dysfunction in the acute phase, patients with VGKC-LE often make a substantial recovery with immunotherapy but may be left with permanent anterograde amnesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 18 publications
(27 reference statements)
4
50
0
Order By: Relevance
“…The link between focal CA3 atrophy and impaired autographical episodic memory elaborates on the chronic behavioural phenotype of VGKC-complex antibody-mediated limbic encephalitis to include amnestic pathology beyond reports of impaired verbal and figural memory (Frisch et al , 2013; Bettcher et al , 2014; Butler et al , 2014; Malter et al , 2014). Critically, prior reports did not focus on specific mnemonic operations that are reliant upon CA3 integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between focal CA3 atrophy and impaired autographical episodic memory elaborates on the chronic behavioural phenotype of VGKC-complex antibody-mediated limbic encephalitis to include amnestic pathology beyond reports of impaired verbal and figural memory (Frisch et al , 2013; Bettcher et al , 2014; Butler et al , 2014; Malter et al , 2014). Critically, prior reports did not focus on specific mnemonic operations that are reliant upon CA3 integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Encephalitis in patients positive for VGKC-complex, LGI1, or CASPR2 antibodies can present with inflammatory changes of the medial temporal lobe on acute MRI (Kotsenas et al , 2014), and whole-hippocampal atrophy in the convalescent and chronic phases (Irani et al , 2013; Malter et al , 2014). Neuropsychological assessment, following immunomodulation therapy, reveals substantial variability in outcome (Chan et al , 2007; Frisch et al , 2013; Bettcher et al , 2014; Butler et al , 2014; Malter et al , 2014), unlike the more severe deficits often observed in progressive medial temporal lobe diseases such as Alzheimer’s disease (Wolk et al , 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Residual memory function was predicted by the antibody titer at presentation. 16 One study in 18 patients with VGKC-LE in which the effect of subtypes was investigated, stated that, although all subgroups improved, memory scores only normalized in 6 patients (33%) and LGI1-Ab(þ) patients were left with significantly poorer memory than the other 2 subgroups (CASPR-2-Ab[þ] or LGI/ CASPR-2-Ab[À]). They state that most patients with VGKC-LE become seizure-free with pulsed monthly methylprednisolone, but memory outcome is less favorable.…”
Section: Discussionmentioning
confidence: 99%
“…At follow-up after 5–70 months, 11 of 17 patients still had impaired function of at least one memory domain. Another study evaluated cognitive function of 19 patients with VGKC antibodies (9 LGI1, 1 Caspr2, 9 not tested) using standardised neuropsychological assessment 10. Similarly, the cohort had significant impairment of memory, processing speed and executive function at the initial visit 16–377 days after symptom onset, while language and perceptual organisation were not affected.…”
Section: Cognitive Impairment and Vgkc Complex Antibodiesmentioning
confidence: 99%
“…Similarly, the cohort had significant impairment of memory, processing speed and executive function at the initial visit 16–377 days after symptom onset, while language and perceptual organisation were not affected. At visit 2 ranging from 3 to 44 months after the first assessment, processing speed and executive function had normalised, while at least a third of patients were left with permanent anterograde amnesia 10. A third study addressing cognitive impairment in VGKC antibody-associated limbic encephalitis examined 15 patients and found impairments in attentional–executive functions and verbal and non-verbal memory 1–23 months after symptom onset, mostly in two or three domains 11.…”
Section: Cognitive Impairment and Vgkc Complex Antibodiesmentioning
confidence: 99%